Delimitacyjno-semantyczne wykładniki graficzne renesansowej krytyki tekstu w Nowym Testamencie (1551, 1552) w przekładzie Stanisława Murzynowskiego - Lisowski, Tomasz (Slavia Occidentalis, 2015)
Nowy Testament (The New Testament) translated by Stanisław Murzynowski was published in Königsberg (Królewiec) in East Prussia in 1551 (part one) and in 1552 (part two). It was the first Polish translation of the New Testament (and the Bible in general) delivered in line with the Protestant sola Scriptura doctrine from Greek, the source language. In his endeavour to faithfully (precisely) reflect the sense of the original in the Polish language, the translator subjected the text to a philological review. The effects of his considerations are made available to the readers and introduced to the translation of the Bible by means of a system of graphic devices which delimit the text and add an intellectual aspect to it. In most general terms, the devices indicate when the Polish translation departs from the Greek original as a result of the system and semantic differences between the two languages; they pinpoint the semantic and lexical polarization of the Polish translation of the biblical message as a result of the translator- cum-philologist’s critical approach to the original text. As a printed text, Nowy Testament translated by Stanisław Murzynowski represents a closed work with precisely selected wording. Its core part containing the New Testament message in Polish consists of the primary text i.e. the translation of the New Testament into the Polish language and an intermittent subordinate part dedicated to the marginalia. The delimitation and semantic devices introduce visual order to the printed text, fostering the reader’s perception; they are also non-verbal expressions of the inter-textual relations and references to external texts which contributed to the then universe of knowledge. Therefore, the devices provide an intellectual aspect to the Polish language offered by Stanisław Murzynowski.